(untitled) (Journal of Hama University, 2024)
The research aimed to identify the degree of organizational commitment of the principals of the schools of the second cycle of basic education, the level of their job performance, and the level of their job performance, and to study the relationship between organizational commitment and job performance they have from the point of view of teachers in Latakia city. The research sample included (278) male and female teachers for the academic year 2022/2023. To achieve the purpose of the research, two tools were built, the first questionnaire consisting of (28) phrases measuring the degree of organizational commitment of managers, and a second questionnaire consisting of (68) statements measuring the job performance of managers distributed into six areas. The results of the research showed that the degree of organizational commitment of the principals of the schools of the second cycle of basic education from the point of view of teachers in Latakia city was average, and that the level of job performance also average, as well as the results showed a strong and statistically significant positive relationship between the degree of organizational commitment and the level of job performance among the principals of schools of the second cycle of basic education. The research also made suggestions, including enhancing the culture of organizational commitment among school principals, as this has an impact on improving job performance in the school.